Safety Evaluation of Lawsonia inermis on Physiological, Andrological and Haematological Parameters of Male Wistar Rats - Aremu, Abdulfatai; Oridupa, Olayinka Ayotunde; Akorede, Ganiu Jimoh; Olatumji, Aishat Omobolanle; Basiru, Afisu; Ahmed, Akeem Olayiwola; Raufu, Ibrahim Adisa (Universitas Airlangga, 2022)
The leaves of Lawsonia inermis Linn are used in the treatment of many diseases such as diabetes, poliomyelitis, measles and gynecological disorders such as menorrhagia, vaginal discharge and leucorrhoea. This study was designed to investigate the safety evaluation of Lawsonia inermis Linn leaves (acutely and sub-chronically) on physiological, biochemical and histopathological changes seen in Wistar rat. Acutely, female rats were divided into four groups (n=3) and treated as thus A (untreated control); B (1000 mg/kg); C (2000 mg/kg) and D (5000 mg/kg). Sub-chronically, 25 male Wistar rats were grouped into five (n=5). Groups: A (control), B (100 mg/kg); C (200 mg/kg); D (400 mg/kg) and E (800 mg/kg). Lawsonia inermis Linn leaves have a wide safety margin (>5000mg/kg) and no mortality or visible toxic reaction was observed in acute phase. Lawsonia inermis extract did not inhibit physiological weight gain, except the highest dose that caused some weight loss. Haematological result showed that PVC, RBC, haemoglobin and platelets had no significant (P>0.05) effect unlike white blood cell and differentials (neutrophils, lymphocytes and monocytes) which decrease significantly (P <0.05) across all the treated groups compared to untreated control. Serum chemistry showed a significant (P <0.05) decrease AST. ALT, ALP, creatinine, urea, Total protein and Total bilirubin had no significant (P <0.05) effects. Serum electrolytes; calcium ion, potassium ion, sodium ion and chloride ion had no significant (P <0.05) changes. Lawsonia inermis is safe at acute administered dosages while nephrotoxicity and spermiotoxicity may occur following subchronic administration.